Age-specific Multimorbidity Patterns and Burden on All-Cause Mortality and Public Direct Medical Expenditure: A Retrospective Cohort Study - Sabrina Nan Hong; Francisco Tsz Tsun Lai; Boyuan Wang; Edmond Pui Hang Choi; Ian Chi Kei Wong; Cindy Lo Kuen Lam; Eric Yuk Fai Wan (Journal of Epidemiology and Global Health, 2024)
Abstract Objective To evaluate age-specific multimorbidity patterns and morbidity burden on mortality and healthcare expenditure across age groups. Patients and Methods Retrospective observational study between January 1, 2009 to December 31, 2017 using electronic health records in Hong Kong: Individuals were stratified by age (< 50, 50–64, 65–79, ≥ 80), and sub-classified by number of morbidities (0, 1, 2, 3, ≥ 4) out of 21 common chronic conditions. Clustering analyses were conducted to identify specific patterns of multimorbidity. Association between the number as well as combinations of morbidities and all-cause mortality and public expenditure was examined. Results 4,562,832 individuals with a median follow-up of 7 years were included. Mental disorders were the top morbidities among young individuals, while cardiovascular diseases were prevalent in the elderly. An increased number of morbidities was associated with a greater relative risk for mortality and medical expenditure, and this relationship was stronger among younger patients. Compared to individuals in the same age group without morbidity, the hazard ratios (HR; 95% CI) of all-cause mortality in patients aged < 50 and ≥ 80 with two comorbidities 3.81 (3.60–4.03) and 1.38 (1.36–1.40), respectively, which increased to 14.22 (9.87–20.47) and 2.20 (2.13–2.26), respectively, as the number of morbidities increased to ≥ 4. The stroke-hypertension cluster was shown to be associated with the highest HR of mortality 2.48 (2.43–2.53) among all identified clusters arising from the clustering analysis. Conclusion Given the stronger association between multimorbidity and all-cause mortality and greater opportunity costs in younger populations, prevention and management of early-onset multimorbidity are warranted. (248 words)